How do you solve 7(6-3k)=147?

3 Answers
Aug 9, 2017

See a solution process below:

Explanation:

Step 1) Divide each side of the equation by color(red)(7) to eliminate the need for the parenthesis while keeping the equation balanced:

(7(6 - 3k))/color(red)(7) = 147/color(red)(7)

(color(red)(cancel(color(black)(7)))(6 - 3k))/cancel(color(red)(7)) = 21

6 - 3k = 21

Step 2) Subtract color(red)(6) from each side of the equation to isolate the k term while keeping the equation balanced:

-color(red)(6) + 6 - 3k = -color(red)(6) + 21

0 - 3k = 15

-3k = 15

Step 3) Divide each side of the equation by color(red)(-3) to solve for k while keeping the equation balanced:

(-3k)/color(red)(-3) = 15/color(red)(-3)

(color(red)(cancel(color(black)(-3)))k)/cancel(color(red)(-3)) = -5

k = -5

Aug 9, 2017

See below

k=-5

Explanation:

To solve 7(6−3k)=147, first divide both sides by 7

7(6−3k)-:7=147/7" "rArr" "6−3k=21

next subtract 6 from both sides" "6−3k-6=21-6

rArr" "-3k=15

now divide both sides by -3" "-3k/-3=15/-3" "rArr k=-5

Aug 9, 2017

k=-5

Refer to the explanation for the process.

Explanation:

Solve:

7(6-3k)=147

Expand using the distributive property: a(b+c)=ab+bc.

42-21k=147

Subtract 42 from both sides.

-21k=147-42

Simplify.

-21k=105

Divide both sides by -21.

k=105/(-21)

Simplify.

k=-5